The book of Rumi: 105 stories and fables - "Mafi, Maryam" (Amaryllis Bhopal, 2018)
This fresh prose translation of 105 short teaching stories by Rumi, which form the core of the six-volume Masnavi, explores the hidden spiritual aspects of everyday experience. Rumi transforms the seemingly mundane events of daily life into profound Sufi teaching moments. These prose gems open the mystical portal to the world of the ancient mystic. These stories include well-known and popular tales such as "Angel of Death," "The Sufi and His Cheating Wife," "Moses and the Shepherd," "Chickpeas," and "The Greek and Chinese Painters" as well as the less commonly quoted parables: "The Basket Weaver," "The Mud Eater," and "A Sackful of Pebbles." Rumi's voice alternates between playful and authoritative, whether he is telling stories of ordinary lives or inviting the discerning reader to higher levels of introspection and attainment of transcendent values. Mafi's translations delicately reflect the nuances of Rumi's poetry while retaining the positive tone of all of Rumi's writings, as well as the sense of suspense and drama that mark the essence of the Masnavi